Mechanical properties of normal strength concrete containing oil palm shell as partial aggregate replacement - Siti Nur Aishah Izzati, Khamarruzaman (2018)
Palm oil shell is a one of the huge waste producing from oil palm extraction process. The oil palm shell (OPS) which have natural sized seems to be ideal for substituting aggregates in concrete construction because previous study found that oil palm shells was the organic aggregate which is better impact resistance compared to normal weight aggregate. The purpose of this research is to investigate the optimum percentage of oil palm shell as a partially coarse aggregate replacement and to determine the mechanical properties of oil palm shell concrete such as compressive strength, splitting tensile, flexural and modulus of elasticity. A set of laboratory tests were conducted on normal weight concrete made by coarse aggregate as control sample and OPS concrete with 50% and 100% percentage of OPS as a partial coarse aggregate replacement. The test results showed that OPS concrete with a compressive strength in the range of 16.56 - 60.1 MPa has a splitting tensile strength range of 1.05 – 3.31 MPa, flexural strength range of 3.61 – 8.95 MPa and modulus of elasticity range of 5.32 – 39.35 GPa. Similarly, for compressive strength, flexural strength, splitting tensile strength and modulus of elasticity, the trends of those tests decreases dramatically as the OPS replacement were increased. This indicated that when the high quantity of OPS is used in concrete mix design, it has an impact on wet properties which is workability and it can potentially reduce all the strength properties of concrete. However, the normal strength G30 OPS concrete can be produced with the 50% of partially coarse aggregate replacement in concrete.